A Multipurpose Robotic Vehicle for the Rescue of Persons and Interventions in Emergency Situations - David Rehak; Ales Dudacek; Pavel Polednak (Communications - Scientific letters of the University of Zilina, 2013)
At present, multipurpose robotic vehicles represent the best possible solution for the rescue and transport of persons in a state of traumafrom places in difficult-to-access terrain, in poor weather conditions and in emergency situations. It is a case of complementary means supplementingthe equipment for rescue and emergency response that already exists or is being developed on the basis of a concept drawn in theframework of Integrated Emergency System of the Czech Republic. As a multipurpose means, the vehicle can be used for unmanned remoteinvestigations into situations, for unmanned rescue and materials transport. Simultaneously, a modification to vehicles for places accessiblemerely by rail is designed.